Distinguishing factors that influence attendance and behaviour change in family‐based treatment of childhood obesity: A qualitative study. Issue 1 (24th July 2020) - Watson, Paula M.; Dugdill, Lindsey; Pickering, Katie; Hargreaves, Jackie; Staniford, Leanne J.; Owen, Stephanie; Murphy, Rebecca C.; Knowles, Zoe R.; Johnson, Laura J.; Cable, N. Timothy
Abstract : Objectives: For the effective treatment of childhood obesity, intervention attendance and behaviour change at home are both important. The purpose of this study was to qualitatively explore influences on attendance and behaviour change during a family‐based intervention to treat childhood obesity in the North West of England (Getting Our Active Lifestyles Started (GOALS)). Design: Focus groups with children and parents/carers as part of a broader mixed‐methods evaluation. Methods: Eighteen focus groups were conducted with children ( n = 39, 19 boys) and parents/carers ( n = 34, 5 male) to explore their experiences of GOALS after 6 weeks of attendance (/18 weeks). Data were analysed thematically to identify influences on attendance and behaviour change. Results: Initial attendance came about through targeted referral (from health care professionals and letters in school) and was influenced by motivations for a brighter future. Once at GOALS, it was the fun, non‐judgemental healthy lifestyle approach that encouraged continued attendance. Factors that facilitated behaviour change included participatory learning as a family, being accountable and gradual realistic goal setting, whilst challenges focussed on fears about the intervention ending and a lack of support from non‐attending significant others. Conclusions: Factors that influence attendance and behaviour change are distinct and may be important at different stages of the family's change process. Practitioners are encouraged to tailor strategies to support both attendance and behaviour change, with a focus on whole family participation within and outside the intervention.